ANALISIS DAMPAK PEMBELAJARAN VIRTUAL SEBAGAI TINDAKAN PENCEGAHAN COVID-19 DI PERGUTUAN TINGGI - Eri Susanto (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
This research was conducted to determine the impact of virtual learning as a preventive measure for COVID-19 in higher education. This research uses the basis of qualitative methods with literature studies from several sources, both printed and electronic, as well as accredited scientific journals. The article criteria used in this study are articles that describe virtual learning in college students and have a complete section. The search mechanism is using the Google Scholar database using the keywords